THE CONCEPTION OF CREATING VIRTUAL LABORATORY WORKSHOPS USING WEB - TECHNOLOGY - Сав’юк, Лариса Олександрівна; Рогач, Артур Олегович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Advantages of introduction in the educational process of students of technical specialties of virtual laboratory practical works on the basis of modern vehicle-programmatic facilities of firm National Instruments are considered.